2021
DOI: 10.1242/jcs.258699
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 17, an ancient SNARE paralog, plays different and conserved roles in different organisms

Abstract: Mammalian syntaxin 17 (Stx17) has several functions, other than membrane fusion, including mitochondrial division, autophagosome formation and lipid droplet expansion. Different from conventional syntaxins, Stx17 has a long C-terminal hydrophobic region with a hairpin-like structure flanked by a basic amino acid-enriched C-terminal tail. Although Stx17 is one of the six ancient SNAREs and present in diverse eukaryotic organisms, it has been lost in multiple lineages during evolution. In the present study, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Expression of SYX-17::mCherry driven by syx-17 endogenous promoter is evident in various somatic tissues, including muscles, intestine and neuronal cells ( Figure S2A,B ). In agreement with previous studies in flies and humans, we find that the C. elegans SYX-17 colocalizes with mitochondria both in muscle and neuronal cells ( Figure 1 C and Figure S2A , respectively) [ 31 , 39 ]. Next, we generated transgenic animals expressing VAMP-7 tagged with GFP in muscle cells and found that a significant portion of VAMP-7 is found in proximity to mitochondria while it co-localizes with small TOMM-20-positive vesicles, reminiscent of mitochondrial-derived vesicles (MDVs)(TOMM-20) ( Figure 1 D) [ 31 , 40 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Expression of SYX-17::mCherry driven by syx-17 endogenous promoter is evident in various somatic tissues, including muscles, intestine and neuronal cells ( Figure S2A,B ). In agreement with previous studies in flies and humans, we find that the C. elegans SYX-17 colocalizes with mitochondria both in muscle and neuronal cells ( Figure 1 C and Figure S2A , respectively) [ 31 , 39 ]. Next, we generated transgenic animals expressing VAMP-7 tagged with GFP in muscle cells and found that a significant portion of VAMP-7 is found in proximity to mitochondria while it co-localizes with small TOMM-20-positive vesicles, reminiscent of mitochondrial-derived vesicles (MDVs)(TOMM-20) ( Figure 1 D) [ 31 , 40 ].…”
Section: Resultssupporting
confidence: 93%
“…Although the presence of SYX-17 on mitochondria facilitating mitochondrial fission was shown to be conserved in nematodes, flies and mammals, its contribution to autophagy has been disputed [ 39 ]. Therefore, we sought to determine whether endogenous SYX-17 regulates basal autophagy in C. elegans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation